Playing for pizza - Grisham, John.; Welch, Christopher Evan. (Westminster, Md. : Books on Tape, 2007)
A former American football star joins the Parma Panthers to play football in a small town in Italy.
Unabridged.
Compact discs.
Read by Christopher Evan Welch.
Keywords: Quarterbacks (Football) -- Fiction; Americans -- Travel -- Italy -- Fiction; Parma (Italy) -- Social life and customs -- Fiction; Audiobooks; Football stories